Indonesia's Economic Strategy in Facing the Complexity of the South China Sea - Ayu Pertiwi; Guntur Eko Saputro (CV. Rayyan Dwi Bharata, 2023)
Geopolitical and geomaritime dynamics in the region are hot issues today, one of which is happening in the South China Sea (SCS). Various countries directly adjacent to the SCS even claim ownership of these waters. The dispute that occurred in the SCS has not reached an end point until now since it first occurred. Various efforts have been made to maintain the stability of the region and prevent major conflicts from occurring. The purpose of this study is to find out what strategies and efforts Indonesia has made in dealing with various problems that occur in the South China Sea. The research method used is descriptive qualitative using data obtained from various sources, such as national and international journals, books, and other relevant sources. The result of this research is that many strategies that have been carried out by the Indonesian government have started from diplomatic strategies to reducing military power in border areas bordering the South China Sea.